Luminescence and creation of electron-hole trapping centers in alkali metal sulfates activated by Pb2+ impurity - Nurakhmetov, T; Shamieva, R.K.; Salikhodzha, Zh.M.; Temirkulova, N.I.; Alibay, T.T.; Sadykova, B.M.; Yussupbekova, B.N.; Kabdulkak, A.A. (Eurasian Journal of Physics and Functional Materials, 2026)
The nature of the impurity emission and the process of creating intrinsic and impurity electron-hole trapping centers were studied by spectroscopic and thermal activation methods in Na2SO4 - Pb and K2SO4 - Pb phosphors. The combined radiative electronic state is formed from intrinsic SO3− 4 - SO− 4 and impurity Pb+ - SO− 4 electron-hole trapping centers in UV-irradiated phosphors with a photon en- ergy of 6.2 eV at 80 K. Emissions of 3.2 eV and 3.6 eV resulting from irradiation with photons with an energy of 6.2 eV are associated with intracenter transitions of 3p1 - 1s0 in Pb2+ located in nonequiva- lent positions of the Na2SO4 latticeRecommended CitationNurakhmetov, T. N.; Shamieva, R. K.; Salikhodzha, Zh. M.; Temirkulova, N. I.; Alibay, T. T.; Sadykova, B. M.; Yussupbekova, B. N.; and Kabdulkak, A. A. (2024) "Luminescence and creation of electron-hole trapping centers in alkali metal sulfates activated by Pb2+ impurity," Eurasian Journal of Physics and Functional Materials: Vol. 8: No. 1, Article 4.DOI: https://doi.org/10.32523/ejpfm.2024080104